Stakeholders as Researchers: Cooperative Inquiry and the Leadership Role of School Librarians - Mardis, Marcia A.; Everhart, Nancy (Qualitative and Quantitative Methods in Libraries; Vol 2 No 2 (2013): June 2013 Issue, 2017)
Cooperative inquiry (CI), a form of qualitative research used in community building, has not been used with school librarians and in very few schools. Through the lens of Formative Leadership Theory, the researchers studied the abilities of three new school librarians trained in CI and leadership to engage in collaborative problem solving for technology-related school challenges. Due to internal and external factors, participants experienced various levels of success in the CI process and gained positive recognition from their colleagues for exhibiting traits of formative leaders.